Explosive Price and Tail Risk in Asean-5 Islamic Equity Markets - Arie Sukma (EKONOMIKA SYARIAH : Journal of Economic Studies, 2026)
This study examines whether explosive prices are associated with extreme tail risk in Islamic equity markets across five ASEAN countries. Using the GSADF framework to identify explosive episodes and a GARCH–EVT approach to measure tail risk, it constructs a panel dataset covering Indonesia, Malaysia, the Philippines, Thailand, and Singapore over 2008–2025. The analysis evaluates four specifications: contemporaneous effects, forward-looking dynamics, post-collapse adjustments, and the frequency of extreme events. The results reveal no consistent relationship between explosive price dynamics and tail risk. The baseline model shows a small contemporaneous effect of approximately 9% of average monthly tail risk, but forward-looking specifications provide no predictive evidence, and post-collapse dynamics do not increase downside risk. Conditional volatility emerges as the dominant driver of tail risk, with substantially larger magnitudes. The findings also indicate strong cross-market heterogeneity, where more developed markets, such as Singapore, experience reductions in both the intensity and frequency of tail events during explosive episodes. These results are robust across alternative volatility specifications, including GJR-GARCH models. The evidence suggests a decoupling between price dynamics and risk formation. These findings have important implications for Islamic financial stability analysis and show that risk in Islamic financial markets is shaped more by volatility dynamics and market structure than by price behavior alone